The Influence of Social, Economic and Environmental Aspects on the Welfare of Traditional Diamond Mining in Cempaka District, Banjarbaru City, Indonesia - Wijokongko, Bayu; Yunani, Ahmad; ., Hafizianoor; Sopiana, Yunita (Journal of Ecohumanism, 2024)
The abundance of natural resources in the form of mining minerals has made traditional diamond mining activities in Cempaka Sub-district a mainstay of Banjarbaru City in improving the welfare of the mining community. In addition, traditional diamond mining is able to contribute to regional PAD, and another added value of traditional diamond mining activities is to become a natural tourist attraction (ecotourism) for foreign and domestic tourists to see diamond mining more closely. This study aims to: (1) Analyze the influence of social aspects on the welfare of traditional diamond miners in Cempaka Sub-district; (2) Analyze the influence of economic aspects on the welfare of traditional diamond miners in Cempaka Sub-district; and (3) Analyze the influence of environmental aspects on the welfare of traditional diamond miners in Cempaka Sub-district. This research uses a Quantitative approach aimed at being able to analyze the influence of Social Aspects on Welfare, Economic Aspects on Welfare, and Environmental Aspects on Welfare in traditional diamond mining communities in a complete and comprehensive manner. The research stages include the Survey Method using Primary and Secondary Data. Primary data is obtained from questionnaire data (questionnaire) of respondents (mining community), while secondary data is obtained from the mining office and related agencies. The research consists of three aspects, including: (1) Research Aspect I which analyzes the influence of Social Aspects on the Welfare of traditional diamond miners in Cempaka Sub-district using respondents in three hamlets namely Ujung Murung, Luka’as, and Pumpung. All 234 households in these three hamlets were taken as samples based on the sample technique with a reachable population. Respondents taken as samples were all households working as miners. The variables observed were the Social Aspects on the Welfare of traditional diamond miners, which were analyzed using the Path Analysis Parametric Statistical approach; (2) Research Aspect II, which analyzed the influence of Economic Aspects on the Welfare of traditional diamond miners in Cempaka Sub-district; and (3) Research Aspect III, which analyzed the influence of Environmental Aspects on the Welfare of traditional diamond miners in Cempaka Sub-district, using the same respondents as in Research Aspect I. The observed variables are selected data from questionnaires filled out by the mining community, which are analyzed using Regression Path Analysis and Scoring. Questionnaires from Social Aspects, Economic Aspects, and Environmental Aspects were used to see the significance of the influence of these three aspects on improving the Welfare of Traditional Diamond Miners.